Prevención de Caídas: ¡Reducir los Riesgos! - Jennifer Hillan (EDIS, 2006)
Revised! FCS2231-Span, a 1-page fact sheet by Jennifer Hillan, is the Spanish Language version of "Fall Prevention: Reduce Your Risk!" It is a crossword puzzle to help participants find out how much they know about lifestyle factors that affect their risk of falling. Published as part of the Elder Nutrition and Food Safety (ENAFS) program by the UF Department of Family Youth and Community Sciences, October 2004. Revised May 2006.